Remote Vision (poetry 1999-2015) - De Francesco, Alessandro (punctum books, 2020)
"Remote Vision represents, in English and Italian, the most significant works in poetry and conceptual writing produced by Alessandro De Francesco to date. It is both a coherent book and the most exhaustive collection of his poetry ever published in any language. All sections have been rearranged for this publication, with each one containing the complete English text followed by the complete Italian version. The texts have been beautifully translated by poets and Brown University alumni Belle Cushing and Dusty Neu, under the coordination of the acclaimed poet and Comparative Literature scholar Forrest Gander. Remote Vision condenses and presents under a new light the conceptual and emotional intensity of Alessandro De Francesco's poetry."